2016
DOI: 10.1007/s10529-016-2090-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel bifunctional Δ12/Δ15-fatty acid desaturase gene from Rhodosporidium kratochvilovae

Abstract: RKD12 is a novel bifunctional ∆(12)/∆(15)-desaturase gene, and the increased RKD12 mRNA expression level and PUFAs content at low temperature might be helpful for the cold adaptation of YM25235.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Subsequently, GLA is synthesized by introducing a double bond into LA using a delta-6 desaturase. Thus, three desaturases, the delta-9, delta-12 and delta-6, accomplish the desaturation processes in GLA synthesis [5, 13, 14]. Genes coding for those desaturases have been cloned from diverse organisms ranging from prokaryotes to higher eukaryotes, and overexpressed in several hosts, including microalgae, yeasts and plants [8, 1316].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, GLA is synthesized by introducing a double bond into LA using a delta-6 desaturase. Thus, three desaturases, the delta-9, delta-12 and delta-6, accomplish the desaturation processes in GLA synthesis [5, 13, 14]. Genes coding for those desaturases have been cloned from diverse organisms ranging from prokaryotes to higher eukaryotes, and overexpressed in several hosts, including microalgae, yeasts and plants [8, 1316].…”
Section: Introductionmentioning
confidence: 99%
“…The bifunctional FADS12 enzyme has been widely characterized as being responsible for converting the OA and LA fatty acid substrates to LA and ALA, respectively, in many species [17,20,21]: functional analysis results showed that FADS12 from Rhodosporidium kratochvilovae converted 11.4% of OA to LA, and 19.1% of LA to ALA; Wei et al [20] reported that FADS12 from Rhizopus arrhizus had a high conversion rate of 16.0% for OA when it was expressed in yeast; and the conversion rate of OA by FADS12 from Mortierella alpina 1S-4 was approximately 24.1%, and that of LA was 36.8%. FADS12 isolated from G. candidum in cheese in this study was also bifunctional for both OA and LA, and we found from our functional analysis that GcFADS12 should continually catalyze the product (LA) of OA to ALA.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the molecular mechanism, substrate specificity and catalytic activity for FADS6 were analyzed and applied to PUFA synthesis . FADS12 is a key bifunctional membrane‐bound desaturase that converts oleic acid (OA, 18:1 Δ9 ) to linoleic acid (LA, 18:2 Δ9,12 ) and LA to α‐linolenic acid (ALA, 18:3 Δ9,12,15 ) by introducing a double bond between the carbons 12 and 13 from the carboxyl end of the substrate in the biosynthesis of EFAs . The genome of G. candidum has been sequenced and submitted to the GenBank database (LOCUS: CCBN010000001) by Casaregola, and we found from its genome sequence that there was a sequence encoding Δ12 fatty acid desaturase of G. candidum ( GcFADS12 ).…”
mentioning
confidence: 99%
“…Delta 12 fatty acid desaturase ( FADS12 ) plays a key role in the synthesis of EFAs during fermentation. FADS12 is a key membrane-bound desaturase that converts oleic acid [OA, 18:1 Δ9 ] to linoleic acid [LA, 18:2 Δ9,12 ] by introducing a double bond between carbons 12 and 13 in the carboxyl end of the substrate in the biosynthesis of EFAs (Cui et al, 2016; Lee, 2016; Rodríguez-Rodríguez, 2016). As a rate-limiting enzyme, FADS12 plays an important role in the metabolism of PUFAs, and its activity directly affects the level and distribution of EFAs in cheese.…”
Section: Introductionmentioning
confidence: 99%